Effect of Clove Weight and Soil Amendments on Yield and Quality of Garlic Bulbs - MANISH KUMAR; SHIPRA GHARWAL; PALAK SHARMA; CHERRY NALWA (Seed Research, 2026)
The experiment was conducted during Rabi season of 2017-18 at Khaltoo farm of Department of Seed Science and Technology, Dr. Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Solan, H.P. India and was laid out in Randomized Block Design (factorial) with three replications of each treatment combination. The observations were recorded on plant height, number of leaves per plant, bulb yield (kg/plot and q/ha), diameter of bulb, weight of clove, TSS etc. Analysis of variance showed significant differences among all treatment combinations for all the traits under study. Highest bulb yield per plot was obtained with the treatment combination S3T2 (clove weight of >5g and vermicompost @5 kg). Clove weight S3 (>5g) and soil amendment T2 (vermicompost @5 kg) independently also gave the best results for most of the growth and yield characters.